SUN-409 Subclinical Hypothyroidism in Hospitalized Patients with Chronic Heart-Failure or Chronic Renal-Failure Is Most Probably Not Due to Thyroid Disease - Bashkin, Amir (J Endocr Soc, 2020)
Introduction: Subclinical hypothyroidism is common in chronic diseases such as heart failure and advanced chronic renal failure. It is unclear whether this is a thyroid disease or an isolated TSH elevation. The goal of this study was to investigate the prevalence of worsening thyroid function in these patients with recurrent admissions. Methods: We performed a retrospective review of medical records of hospitalized patients in non-surgical wards from 2013–2016. First, all patients with TSH levels above the normal range (4.95 mIU/L) and up to 12 mIU/L with FT4 levels in the normal range were identified. We then investigated which of these patients were re-hospitalized at least once within at least six months. According to data from the re-hospitalization, an increase in TSH level above 12 mIU/L or initiation of levothyroxine treatment was defined as worsening of thyroid function. Patients treated with a drug affecting thyroid function or with a known thyroid disease prior to first hospitalization were excluded from the study. Chronic heart failure and chronic renal failure were determined according to reported diagnosis and drug treatment. Chronic renal failure patients were included if the glomerular filtration rate (GFR) in the first hospitalization was below 30 ml/min/1.72 square meter. Results: Overall, 90,199 TSH tests were sent from the non-surgical wards, most of them as part of the admissions profile. Of these, 2,116 hospitalizations met the inclusion criteria of the first hospitalization. In the final analysis, 126 inpatients with at least one re-hospitalization were included, of whom 43 (34.1%) had chronic heart failure and 22 (17.5%) had chronic renal failure. According to the most recent re-hospitalization, thyroid function was worse in 11(8.7%), 4 (9.3%) and 2 (9.1%) patients of the total, heart failure and renal failure groups respectively. The TSH level was found to be normal in re-hospitalization in 81.4% of those with heart failure and 86.4% of those with renal-failure. No association between heart failure or renal-failure and thyroid function worsening was found (p = 1.00 for both). Of 34 patients with chronic heart failure re-hospitalized after 1/2-1 year, in 29 (85.3%) the repeated TSH was normal, in 3 (8.8%) it was unchanged and in 2 (5.9%) it was worse. In most re-hospitalization the worsening was due to initiation of Levothyroxin treatment and because of the retrospective nature of the study we cannot be sure whether the initiation was justified; therefore, it is likely that the worsening percentage is even lower. Conclusions: An isolated TSH elevation in hospitalized patients with past medical history of chronic heart-failure or chronic renal failure does not indicate thyroid disease, in most cases.